The impact of COVID-19 on sports cardiology - Lander, B.; Engel, D. J.; Phelan, D. M. (Sports Cardiology, 2021)
The COVID-19 pandemic in early 2020 necessitated a global shutdown of organized sports from the recreational level to the Olympic Games. Concerns of potential cardiac sequelae of COVID-19 have created significant challenges for sport and health organizations to design and implement safe return-to-play (RTP) processes for athletes. In response, American College of Cardiology expert consensus RTP screening algorithms have been generated, and updated, for athletes testing positive for COVID-19. This chapter will review the background data forming the basis and impetus for these RTP screening recommendations, provide strategies to enhance the appropriate use and interpretation of the cardiovascular diagnostic components of the screening algorithms, and present insights gained from experience with the implementation of these RTP recommendations that has allowed safe return to sport.